1991
DOI: 10.1002/ar.1092290311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on the neuroglial cells and pericytes within area 17 of the rhesus monkey cerebral cortex

Abstract: An electron microscopic analysis has been carried out to compare the neuroglial cells and pericytes within the primary visual cortex, area 17, of young (5-6 years) and old (25-35 years) rhesus monkeys. All of the neuroglial cell types accumulate inclusions within their cytoplasm as they age, and the inclusions within the astrocytes and oligodendrocytes are essentially characteristic of those cell types. The astrocytes probably acquire their inclusions by phagocytosis, and it is suggested that the inclusions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
139
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 27 publications
16
139
3
Order By: Relevance
“…In specific cell types, different authors have reported both hyperplasia of human and rat astrocytes (Lolova, 1991;Amenta et al, 1994) and also hypertrophy of these cells. Increases with age have also been described in glial size (Björklund et al, 1985) and in the number of filaments within astrocytes (Peters et al, 1991). Increases with age in microglial cells and oligodendrocytes have been also reported in the frontal cortex of the rhesus monkey (Peters et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In specific cell types, different authors have reported both hyperplasia of human and rat astrocytes (Lolova, 1991;Amenta et al, 1994) and also hypertrophy of these cells. Increases with age have also been described in glial size (Björklund et al, 1985) and in the number of filaments within astrocytes (Peters et al, 1991). Increases with age in microglial cells and oligodendrocytes have been also reported in the frontal cortex of the rhesus monkey (Peters et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…Other non-neuronal cells such as pericytes and endothelial vascular cells were carefully excluded (Ling and Leblond, 1973;Curcio and Coleman, 1982;O'Kusky and Colonnier, 1982;Sturrock, 1983;Peters et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as nonhuman primates are concerned, stereological analyses of various brain structures strongly indicate that neuron numbers do not decline with age. Although the primary visual cortex of aged rhesus monkeys showed no electron microscopical sign of neuron loss, various types of neuroglial cells and pericytes were affected by age [45]. Also, in nonhuman primates, a decrease in white matter volume, as measured with magnetic resonance imaging, was correlated with an overall cognitive impairment [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the visual system of the monkey, from ganglion cell layer to primary visual cortex, shows no neuronal loss due to aging (Kim et al, 1996(Kim et al, , 1997Peters et al, 1997;Ahmad and Spear, 1993;Peters and Sethares, 1993;Vincent et al, 1989). The main changes due to aging in the monkey brain appear to be a degeneration of myelin and various glial cell types (Peters et al, 1989(Peters et al, , 1991(Peters et al, , 1994.…”
Section: Discussionmentioning
confidence: 99%